Effect of Dissipative and Dispersive DNG Material Coating on the Scattering Behavior of Parallel Nihility Circular Cylinders. (26th April 2011) - Ahmed, Shakeel; Naveed, Muhammad; Ghaffar, Abdul; Syed, Aqeel A.; Naqvi, Q. A.
Abstract : Electromagnetic scattering from coated nihility circular cylinders, illuminated by E -polarized plane wave, is investigated using an iterative procedure. Cylinders are infinite in length. The boundary conditions are applied on the surface of each cylinder in an iterative procedure in order to solve for the field expansion coefficients. The effect of different types of the coating layers including double positive (DPS) and double negative (DNG) on the alteration of the forward and backward scattering has been observed. Specially, the effect of dispersive and dissipative DNG coating layer has been focused. Numerical verifications are presented to prove the validity of this formulation by comparison with the published literature.